Investigations of Selected Historically Important Syndromic Outbreaks: Impact and Lessons Learned for Public Health Preparedness and Response - Goodman, Richard A. (American Public Health Association, 2012)
Public health readiness has increased at all jurisdictional levels because of increased sensitivity to threats. Since 2001, with billions of dollars invested to bolster the public health system’s capacity, the public expects that public health will identify the etiology of and respond to events more rapidly. However, when etiologies are unknown at the onset of the investigation but interventions must be implemented, public health practitioners must benefit from past investigations’ lessons to strengthen preparedness for emerging threats. We have identified such potentially actionable lessons learned from historically important public health events that occurred primarily as syndromes for which the etiological agent initially was unknown. Ongoing analysis of investigations can advance our capability to recognize and investigate syndromes and other problems and implement the most appropriate interventions.